Development of a compliant micro gripper : a thesis submitted in partial fulfillment for the degree of Masters of Engineering in the School of Engineering and Advanced Technology, Massey University - Lofroth, Matthew (Massey University, 2019)
Manipulating micro objects simply and effectively has been a widely discussed and challenging task in recent literature for many reasons. Limitations in complex micro fabrication techniques mean creating extremely small tools at the micro scale is very difficult. Adhesion forces also dominate at this scale, causing anything and everything to stick together. This means that even when these tiny structures are created and introduced to the micro world, they quickly become polluted with contaminants and struggle to pick and place particles without said particle adhering to the tool. Indirect methods for micro manipulation exist, however these can be damaging to biological material such as cells, due to unseen forces being focused into a small point. Having the ability to safely manipulate and separate these objects from a culture is crucial to understanding their individual characteristics. Therefore a safe and reliable method for micro manipulation needs to be developed. This project focuses on investigating the current methods used for micro manipulation in order to identify any possible routes towards developing a simple and yet effective means for manipulating micro objects. A modular micro gripping mechanism is proposed in this report, capable of manipulating many different types of objects such as spherical, non spherical or other arbitrary shapes. The proposed micro gripper combines traditional machining techniques with a complex micro fabrication process to produce a modular mechanism consisting of a sturdy, compliant aluminium base in which replaceable silicon and borosilicate glass end effectors are attached. This creates an easily customisable solution for micro manipulation with an array of different micro tips for different applications. A kinematic analysis for the gripper has been provided which predicts the workspace of the gripper given an input actuation. Design parameters of the gripper have also been optimised through various techniques such as FEA (finite element analysis) simulation and the effects of altering individual flexure beam lengths. The gripper is operated by a piezo actuator with a total capable expansion of 19 mm when 150 VDC is applied. This expansion is then amplified by a factor of 8.1 to a maximum tip displacement of approximately 154 mm. Displacement amplification is achieved by incorporating bridge and lever amplifying techniques into the compliant design. The complete micro gripper is then used to demonstrate manipulation tasks on several different target object types including silica micro beads (spherical and non spherical), a human eyelash and a grain of pollen. These tests are performed to investigate the effect of adhesion forces and also to demonstrate the large size range of capable pick and place objects (6 mm to 500 mm).
Keywords: Manipulators (Mechanism); Microelectromechanical systems; Design and construction